Assessing the reach and effectiveness of mHealth: evidence from a reproductive health program for adolescent girls in Ghana - Slawa Rokicki; Günther Fink (BMC, 2017)
Abstract Background While mobile health (mHealth) programs are increasingly used to provide health information and deliver interventions, little is known regarding the relative reach and effectiveness of these programs across sociodemographic characteristics. We use data from a recent trial of a text-messaging intervention on adolescent sexual and reproductive health (SRH) to assess the degree to which mHealth programs reach target adolescent subpopulations who may be at higher risk of poor SRH outcomes. Methods The study was conducted among girls aged 14-24 in 22 secondary schools in Accra, Ghana. The mHealth intervention was an interactive mobile phone quiz in which participants could win phone credit for texting correct answers to SRH questions. We use detailed data on individuals' level of engagement with the program, SRH knowledge scores, and self-reported pregnancy collected as part of the original trial to assess the extent to which engagement and program impact vary across parental education, sexual experience, SRH knowledge deficit, and parental support. Results Eighty-one percent of participants engaged with the mHealth program, with no evidence that the program disproportionally reached better-off groups. The program was effective at increasing knowledge of SRH across all strata. Higher levels of engagement were associated with higher knowledge scores up to year later. There was no significant impact of the program on self-reported pregnancy within subgroups. Conclusion mHealth programs for adolescents have the potential to engage and increase SRH knowledge of adolescent girls across sociodemographic strata, including those who may be at higher risk of poor SRH outcomes. Trial registration ClinicalTrials.gov NCT02031575 . Registered 07 Jan 2014.